2012
DOI: 10.1016/j.bbabio.2011.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Thiol redox requirements and substrate specificities of recombinant cytochrome c assembly systems II and III

Abstract: The reconstitution of biosynthetic pathways from heterologous hosts can help define the minimal genetic requirements for pathway function and facilitate detailed mechanistic studies. Each of the three pathways for the assembly of cytochrome c in nature (called systems I, II, and III) has been shown to function recombinantly in Escherichia coli, covalently attaching heme to the cysteine residues of a CXXCH motif of a c-type cytochrome. However, recombinant systems I (CcmABCDEFGH) and II (CcsBA) function in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 65 publications
(101 reference statements)
1
10
0
Order By: Relevance
“…In prokaryotes, many c-type cytochromes exist in addition to monoheme proteins (17)(18)(19)(20). These are all matured by Systems I and II, consistent with the proposal that only the CXXCH motif is recognized (21)(22)(23)(24). By contrast, the eukaryotic HCCS appears to require a more extended recognition domain than just the CXXCH motif for cytochrome maturation, specifically sequence features or residues located in the cyt c N terminus (see Fig.…”
supporting
confidence: 74%
See 1 more Smart Citation
“…In prokaryotes, many c-type cytochromes exist in addition to monoheme proteins (17)(18)(19)(20). These are all matured by Systems I and II, consistent with the proposal that only the CXXCH motif is recognized (21)(22)(23)(24). By contrast, the eukaryotic HCCS appears to require a more extended recognition domain than just the CXXCH motif for cytochrome maturation, specifically sequence features or residues located in the cyt c N terminus (see Fig.…”
supporting
confidence: 74%
“…Although the bacterial CCM system (i.e. System I) can successfully mature a wide range of mono-and multiheme cytochromes, containing simply a CX n CH motif (where X n ϭ 1-4 intervening residues) (21,24,42,43), additional structural features of eukaryotic cytochromes contribute to the strict substrate specificity of HCCS. For example, previous genetic studies have suggested that the conserved phenylalanine residue in cyt c ␣ helix-1 is critical for HCCS maturation by serving as a determinant for substrate recognition (step 2) because substitution of this residue can result in poor cyt c yields (21, 25) (Phe 11 in human cyt c; the equivalent of this position in bacterial cytochromes is not fully conserved (21, 44)).…”
Section: Discussionmentioning
confidence: 99%
“…E. coli strains (SI Appendix, Table S2) were grown at 37°C in LB broth (Difco) supplemented with the appropriate antibiotics (Sigma-Aldrich) and other medium additives at the following concentrations, unless otherwise noted: carbenicillin, 50 μg·mL Protein Expression and Purification. For HCCS expression (with or without coexpression of cytochrome c), E. coli Δccm strain RK103 (68) or RK112 (69) was used. Starter cultures were initiated from a single colony and grown overnight at 37°C with shaking at 200 rpm in 100 mL of LB medium with the appropriate antibiotics.…”
Section: Methodsmentioning
confidence: 99%
“…CcdA and CcsX are required for thioreduction of apocyt c thiol groups, whereas CcsAB complex transports heme b to the p side of the membrane, recognizes the apocyt c substrates and forms the thioether bonds between the apocyt c and heme b . Substrate specificity of Ccs is not yet fully established, but it may be as broad as the Ccm-System I [32, 33]. …”
Section: Diversity Of Cytochrome C Biogenesis Systemsmentioning
confidence: 99%